Immunity Rights in Public Laws for Indonesia’s Handling of Covid-19 Pandemic - Abdul Madjid (Indian Journal of Forensic Medicine & Toxicology, 2021)
This paper discusses about the regulation of immunity rights that are given to government officials in theirresponse to the outbreak of COVID-19 in Indonesia, seen from the perspective of guilt theory and publiclaws. This right to legal immunity was created with the issuance of Government Regulation in Lieu of Law(Perppu) Number 1 of Year 2020, which was approved and enacted by the People’s Representative Councilof the Republic of Indonesia into law by the ratification of Law Number 2 of Year 2020. Article 27 explicitlystates that government officials, in their execution of this Government Regulation in Lieu of Law, cannotbe prosecuted civilly or criminally if the execution of their tasks is based on good faith and is in line withthe stipulations of legal regulations. This paper uses the normatif legal research with the statute approachand the conceptual approach. The research results shows that there is a certain recognition of regulationsregarding immunity rights. This is affirmed by a verdict of the Constitutional Court, by which accordingto the Constitutional Court, regulation of immunity rights is not in conflict with the concept of rule of law,with several conditions. In addition, although several stipulations in Indonesian positive law that provideimmunity prevent a person from being prosecuted criminally while performing their duties, at a practicallevel, the specifically provided immunity is meaningless if the person in question fulfills the elements of anarticle that stipulates a criminal act, because the intention of a person is the essence of an act, and judges incourt will decide the matter.